Effect of smoking on the development and outcomes of inflammatory bowel disease in Taiwan: a hospital-based cohort study - Bor-Cheng Chen; Meng-Tzu Weng; Chin-Hao Chang; Ling-Yun Huang; Shu-Chen Wei (Scientific Reports, 2022)
Abstract Smoking influences the risks of inflammatory bowel disease (IBD). A hospital-based cohort was conducted to evaluate the effect of smoking on the development and outcomes of IBD, with age, sex and comorbidities matched non-IBD controls from the National Health Interview Survey database of Taiwan. 700 IBD patients (360 ulcerative colitis (UC), 340 Crohn’s disease (CD)) were analyzed for outcomes; and 575 patients (297 UC, 278 CD) were analyzed for prevalence. Smoking prevalence was significantly lower in UC patients than controls (20.9% vs. 30.4%, p < 0.01), but no difference between CD patients and controls (19.8% vs. 22.1%, p = 0.60). UC smokers had fewer admissions (1.6 vs. 2.5, p < 0.05) but higher rates of new cancer development (16% vs. 6.7%, p < 0.05) and mortality (16% vs. 4.9%, p < 0.01) than nonsmokers. CD smokers tended to have higher rates of stricturing and penetrating diseases (p < 0.05), and higher surgery risk (60.3% vs. 38.3%, p < 0.01) than nonsmokers. Smoking prevents UC occurrence and is associated with fewer hospitalization but increases risks of cancer and mortality. By contrast, smoking does not affect CD occurrence but is related to more aggressive behavior which results in a higher surgical rate.